A Multimodal Discourse Analysis of Yeonjun’s “No Labels Part 01” Album Promotion: Human Billboard as Hybrid Advertising on Instagram Reels - Putri Rizki Syafrayani (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2025)
This study examines the use of multimodal resources in Yeonjun’s No Labels Part 01 album promotion through a human billboard campaign disseminated via Instagram Reels. Employing a qualitative descriptive approach, this research applies Multimodal Discourse Analysis (MMDA) to analyze the interaction of linguistic, visual, auditory, and kinetic modes within two official promotional videos released by @txt_bighit. The findings reveal that the campaign constructs meaning through strong multimodal cohesion, where minimalist typography, symbolic color choices, controlled bodily movement, and ambient urban soundscapes work together to convey the ideology of “No Labels.” The absence of spoken language and background music emphasizes authenticity, artistic autonomy, and resistance to conventional K-pop promotional practices. Visual contrasts between Yeonjun’s exposed album imagery and the anonymity of the performers further reinforce themes of individuality and self-definition. This study concludes that hybrid promotional strategies combining offline street performance and online digital circulation function as effective multimodal discourses in contemporary music marketing, contributing to the expansion of MMDA within performative and digital advertising contexts.